Evaluation of the Intracranial Dural Sinuses with a 3D Contrast-enhanced MP-RAGE Sequence: Prospective Comparison with 2D-TOF MR Venography and Digital Subtraction Angiography - Liang, Luxia (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: The diagnosis of dural sinus thrombosis is often difficult because of its variable and nonspecific clinical presentation and the overlapping signal intensities of thrombosis and venous flow on conventional MR images and MR venograms. We compared 3D contrast-enhanced magnetization-prepared rapid gradient-echo (MP-RAGE) sequences with 2D time-of-flight (TOF) MR venography, digital subtraction angiography (DSA), and conventional spin-echo (SE) MR imaging for the assessment of normal and abnormal dural sinuses. METHODS: In a phantom study, a plastic tube with pulsating flow was used to simulate the intracranial dural sinus. With 3D MP-RAGE, a variety of flow velocities, contrast material concentrations, and angulations between the phantom flow tube and the plane of acquisition were tested to measure their relationship to signal-to-noise ratio (SNR). In a clinical study, 35 patients, including 18 with suspected dural sinus thrombosis, were studied with both MR imaging and DSA. Receiver operating characteristic (ROC) analysis was performed in a blinded fashion using DSA as the reference standard. RESULTS: With the phantom, the SNR of flow increased with increasing contrast concentration, but was not affected by the angle between the tube and scan slab. There was no relationship between SNR and velocity when the contrast concentration was 1.0 mmol/L or greater. In the clinical study, dural sinus thrombosis as well as the normal anatomy of the dural sinuses were seen better with 3D contrast-enhanced MP-RAGE than with 2D-TOF MR venography. Three-dimensional contrast-enhanced MP-RAGE showed the highest diagnostic confidence on ROC curves in the diagnosis of thrombosis. CONCLUSION: Three-dimensional contrast-enhanced MP-RAGE is superior to 2D-TOF MR venography and conventional SE MR imaging in the depiction of normal venous structures and the diagnosis of dural sinus thrombosis, and is a potential alternative to DSA.